COMPARATIVE ANALYSIS OF POLITICAL REGIMES IN PEOPLE’S REPUBLIC OF CHINA (PRC) AND REPUBLIC OF CHINA (ROC) - A. P. Boreev (Сравнительная политика)
The article focuses on the comparative analysis of political regimes and regime change within the “third wave” of democratization in the People’s Republic of China (PRC) and the Republic of China (ROC, Taiwan). The study sheds some light on the failure of democratic transition in China’s after the Tiananmen Square protests. In the course of the study, the key features of non-Western political transformation across the Taiwan Strait were identifi ed. As a result, it was found that Confucian political culture leads to neither democracy, nor authoritarian rule, it merely determines institutional design of the political regimes..